A Case of Hypoglycemia with Insulinoma - Hosein Delshad; Amir Keshvarei; Mahmoud Sattari; Mahmoud Gholyaf (پزشکی بالینی ابن سینا, 1998)
Alteration of consciousness is a common problem in clinical practice. Many of pathologic and metabolic disorders can decrease the conciousness level, transient or permanently.